Emotional Deprivation and its relation to Emotional Intelligence among Schooled Adolescents - Haouadef, Rabah; Nassar, Hajar Turki (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to ascertain the nature of the relationship between emotional deprivation and emotional intelligence among schooled adolescents, and the extent to which this relationship was affected by the differences in residential areas (rural, city). Methods: The sample included 80 male and female students who were chosen according to stratified random sampling method from two intermediate schools for the academic year 2022/2023. In order to come up with a hypothesis test, data were processed statistically using Pearson correlation coefficient for the correlation hypothesis (1), and t-test for the differential hypotheses (2, 3). Results: results showed there is a statistically significant correlation between emotional deprivation and emotional intelligence among schooled adolescents, there are no statistically significant differences between adolescents in their scores on the emotional deprivation scale, according to the region variable, and there are no statistically significant differences between adolescents in their scores on the emotional intelligence scale, according to the region variable. Conclusions: It was found that emotional deprivation is related to emotional intelligence among schooled adolescents, emotional fulfilment is one of the most important basic needs for an adolescent, and any nonfulfillment can subject an adolescent to improper development of his/her personality and emotional intelligence. As the effects of deprivation lead to negative psychological and social effects that can remain throughout a lifetime, therefore, parents must pay attention to adolescents, improve the way they treat them, meet their psychological needs, and pay more attention to developing their emotional intelligence.